The Effect of Appointment of Government Employees with Work Agreements on Teachers' Commitment - Santosa, Achadi Budi (J-MPI (Jurnal Manajemen Pendidikan Islam), 2023)
Organizational commitment is a form of employee loyalty in working in an organization. Recently, the phenomenon of turnover among private teachers has occurred frequently, especially after the government made a policy of hiring civil servants with work agreements. This study aims to examine the effect of job satisfaction and work motivation on organizational commitment in private schools in Bantul district. Through a quantitative approach, data collection was carried out by distributing questionnaires to teachers, then analyzed using multiple linear regression. The results show that; 1). there is a significant effect of job satisfaction on organizational commitment of 57.2%; 2). there is an effect of work motivation on organizational commitment of 26.2%; and 3). there is a simultaneous effect of job satisfaction and work motivation on organizational commitment of 71.9%. The suggestion from this study is that school principals need to maintain the commitment of teachers, especially those working in private educational institutions by increasing the job satisfaction factor.